Konflik Batin Tokoh Dalam Novel Teluk Alaska Karya Eka Aryani: Kajian Psikologi Sastra dan Implikasi Pembelajarannya di SMA - Lola Ivanka; Alifiah Nurachmana; Patrisia Cuesdeyeni; Albertus Purwaka; Nerlin Tauke; Lestari Lestari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2023)
What is the id of the main character in the novel Teluk Alaska by Eka Aryani and (2) What is the ego of the main character in the novel Teluk Alaska by Eka Aryani (3) What is the superego of the main character in the novel Teluk Alaska by Eka Aryani (4) How to trigger learning about the inner conflict of the main character in the novel Teluk Alaska by Eka Aryani in high school. The method used is a descriptive method using qualitative analysis which describes the inner conflict that occurs in the main character. Data collection is used by reading and taking notes. The data source for this research is the novel Teluk Alaska by Eka Aryani with 408 pages published by Coconut Books, first printed in 2019. Based on the study and discussion of research results, it can be concluded that the characters Ana and Alister are protagonists who have id, ego and superego personality aspects. The most prominent personality aspect of Ana's character is the superego aspect, so that Ana's character has a patient attitude and is more concerned with other people's feelings than her own. Meanwhile, the most prominent personality aspect of the character Alister is the id aspect, so Alister has a personality that tends to be difficult to control himself and easily influences situations. The novel Teluk Alaska by Eka Aryani is suitable to be used as literature teaching material in high school, it can clearly help and support as a means of supporting the enrichment of students' reading in addition to certain novels which are used as learning material by literature teachers. It can be seen from the perspective of language, mental maturity (psychology) of students, and cultural background.